Local warming and violent conflict in North and South Sudan - Maystadt, Jean-François; You, Liangzhi; Calderone, Margherita Bernal (International Food Policy Research Institute, 2013)
Weather shocks and natural disasters, it has been argued, represent a major threat to national and international security. Our paper contributes to the emerging micro-level strand of the literature on the link between local variations in weather shocks and conflict by focusing on a pixel-level analysis for North and South Sudan at different geographical and time scales between 1997 and 2009. Temperature anomalies are found to strongly affect the risk of conflict. In the future the risk is expected to magnify in a range of 21 to 30 percent under a median scenario, taking into account uncertainties in both the climate projection and the estimate of the response of violence to temperature variations. Extreme temperature shocks are found to strongly affect the likelihood of violence as well, but the predictive power is hindered by substantial uncertainty. Our paper also sheds light on the vulnerability of areas with particular biophysical characteristics or with vulnerable populations.